If it's not what You are looking for type in the equation solver your own equation and let us solve it.
D( x )
4/x-2 = 0
x = 0
4/x-2 = 0
4/x-2 = 0
4*x^-1 = 2 // : 4
x^-1 = 1/2
-1 < 0
1/(x^1) = 1/2 // * x^1
1 = 1/2*x^1 // : 1/2
2 = x^1
x = 2
x = 0
x = 0
x in (-oo:0) U (0:2) U (2:+oo)
(3/x)/(4/x-2) = x // - x
(3/x)/(4/x-2)-x = 0
(3*x^-1)/(4*x^-1-2)-x = 0
(3*x^-1)/(4*x^-1-2)+(-x*(4*x^-1-2))/(4*x^-1-2) = 0
3/x-x*(4*x^-1-2) = 0
2*x+3*x^-1-4 = 0
2*x+3*x^-1-4 = 0
2*x^1+3*x^-1-4*x^0 = 0
(2*x^2-4*x^1+3*x^0)/(x^1) = 0 // * x^2
x^1*(2*x^2-4*x^1+3*x^0) = 0
x^1
2*x^2-4*x+3 = 0
2*x^2-4*x+3 = 0
DELTA = (-4)^2-(2*3*4)
DELTA = -8
DELTA < 0
x in { }
1 = 0
1/(4*x^-1-2) = 0
1/(4*x^-1-2) = 0 // * 4*x^-1-2
1 = 0
x belongs to the empty set
| 5x-20+30=90 | | (x^2+3x-5)/(x^2-8x+15) | | 26+x=90 | | 3(3a-4)=24 | | (x+3/x+2)(x-3/x-2) | | 8y+5=5y+7 | | 20X3/5 | | 8-r=4 | | 12x-2(4x-3)=x+12 | | 5x+5y=-45 | | Y=X^2-X+2 | | Y=-3X^2+12Y | | 2x^4-4x^2-6=0 | | 9*z=63 | | 9*z=7 | | -5(k-4)=-3(k+2) | | r*1=7 | | 2h+16=10h-16 | | 4(c+5)=40 | | y=6x-15 | | -2=4(-15)-7 | | 3=4(3)-7 | | 11=6(0)-15 | | -12-8-(-6)+9= | | 6+3n-4=6n+6-2n | | x+2x+3x=54 | | 6(2x-5)=6 | | 3(x-3)-x=-3 | | log(x+7)(36x+9)=2 | | 4m^2-9m+2= | | 8u=40 | | 5a^2+26a=63 |